2005
DOI: 10.1007/s10764-005-8851-0
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Reproductive Success in Macaca sylvanus in Gibraltar: No Evidence for Rank Dependence

Abstract: The relationship between social rank and reproductive success is one of the key questions for understanding differences in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…However, juveniles spent significantly less time with infants than males and were less often involved in triadic interactions than both males and females. Our relatedness analyses, combined with our knowledge of matriline membership (Kümmerli and Martin 2005), clearly showed that juveniles exclusively handled infants of their own matriline and used these infants mainly in triadic interactions with the infant's mother. Whether and to what extent juveniles use infants to manage relationships with members of their matriline remains somewhat speculative.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, juveniles spent significantly less time with infants than males and were less often involved in triadic interactions than both males and females. Our relatedness analyses, combined with our knowledge of matriline membership (Kümmerli and Martin 2005), clearly showed that juveniles exclusively handled infants of their own matriline and used these infants mainly in triadic interactions with the infant's mother. Whether and to what extent juveniles use infants to manage relationships with members of their matriline remains somewhat speculative.…”
Section: Discussionmentioning
confidence: 70%
“…We established pairwise rank relationships among males and females based on 592 ''ad libitum'' dyadic agonistic interactions collected mainly during the feeding period throughout the study using only dyadic clear dominance interactions (including aggressive and submissive behaviour) (Semple 1998;Kümmerli and Martin 2005). We calculated pairwise rank distances for male and female dominance hierarchies separately.…”
Section: Behavioural Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a more recent study by Kümmerli and Martin (2005) suggested 500 male age to be more important than rank in influencing mating outcome. Since in our study 501 higher-ranking males were also considerably older, any potential age-related effects on male 502 reproductive success as reported by Kümmerli and Martin (2005) and Küster et al (1995) 503 cannot be excluded. Given that age and rank are closely related in the Barbary macaque (Paul 504 1989), as in other macaque species (Sprague 1998 for review), it is in any case difficult to 505 disentangle the effect of rank and age on male reproductive output.…”
Section: Paternity and Male And Female Sexual Behaviour 420mentioning
confidence: 87%
“…Although some studies reported that high-ranking males had higher rates of reproductive success (long-tailed macaques [de Ruiter et al, 1994]; rhesus macaques [Widdig et al, 2004]; toque macaques [Keane et al, 1997]), others failed to find any correlation, sometimes in the same species (Japanese macaques [Inoue et al, 1993]; long-tailed macaques [Shively & Smith, 1985]; rhesus macaques [Berard et al, 1993]). In Barbary macaques, initial studies led to the assumption that mating and, most probably, reproductive success is dependent on a male's social position in the group [Paul, 1989], whereas other studies have yielded contrasting results [Kümmerli & Martin, 2005]. Paul et al [1993] found a relationship between dominance rank and reproductive success, but this relationship was not found when only adult males were considered.…”
Section: Introductionmentioning
confidence: 99%